Bubbles and Crowding-in of Capital via a Savings Glut - Marten Hillebrand; Tomoo Kikuchi; Masaya Sakuragawa (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper uncovers a novel mechanism by which bubbles crowd in capital investment. If capital is initially depressed by a binding credit constraint, injecting a bubble triggers a savings glut. Higher returns in a new bubbly equilibrium attract additional investors who expand investment at the extensive margin. We demonstrate that crowding-in through this channel is a robust phenomenon that occurs along the entire time path after bubbles are injected.
Keywords: E21; E32; E44; 330